ANALISIS KEDALAMAN LAUT PURBA BATU GAMPING GORONTALO BERDASARKAN KANDUNGAN FOSIL FORAMINIFERA BENTONIK - Permana, Aang Panji; Eraku, Sunarty Suly (Bioeksperimen: Jurnal Penelitian Biologi, 2020)
The research location is in the form of highland morphology in the Gorontalo City. Research material in the form of limestone with research methods in the form of field surveys and micropaleontological analysis. The purpose of this research is to find out the bentonic foraminifera fossil species and to know paleobathymetry. The results of the analysis there are four fossil species namely Biloculinella depressa, Cornuspira foliacea, Pyrgo laevis and Rhabdammina discreta. Based on the content of bentonic foraminifera fossils, it can be determined that paleobathymetry is Middle Neritic - Outer Neritic (20-200 meters).